Calcium dependence of damage to mouse motor nerve terminals following oxygen/glucose deprivation - Talbot, Janet D. (2011)
Motor nerve terminals are especially sensitive to an ischemia/reperfusion stress. We applied an in vitro model of this stress, oxygen/glucose deprivation (OGD), to mouse neuromuscular preparations to investigate how Ca(2+) contributes to stress-induced motor terminal damage. Measurements using an ionophoretically-injected fluorescent [Ca(2+)] indicator demonstrated an increase in intra-terminal [Ca(2+)] following OGD onset. When OGD was terminated within 20–30 min of the increase in resting [Ca(2+)], these changes were sometimes reversible; in other cases [Ca(2+)] remained high and the terminal degenerated. Endplate innervation was assessed morphometrically following 22 min OGD and 120 min reoxygenation (32.5 °C). Stress-induced motor terminal degeneration was Ca(2+)-dependent. Median post-stress endplate occupancy was only 26% when the bath contained the normal 1.8 mM Ca(2+), but increased to 81% when Ca(2+) was absent. Removal of Ca(2+) only during OGD was more protective than removal of Ca(2+) only during reoxygenation. Post-stress endplate occupancy was partially preserved by pharmacological inhibition of various routes of Ca(2+) entry into motor terminals, including voltage-dependent Ca(2+) channels (ω-agatoxin-IVA, nimodipine) and the plasma membrane Na(+)/Ca(2+) exchanger (KB-R7943). Inhibition of a Ca(2+)-dependent protease with calpain inhibitor VI was also protective. These results suggest that most of the OGD-induced motor terminal damage is Ca(2+)-dependent, and that inhibition of Ca(2+) entry or Ca(2+)-dependent proteolysis can reduce this damage. There was no significant difference between the response of wild-type and presymptomatic superoxide dismutase 1 G93A mutant terminals to OGD, or in their response to the protective effect of the tested drugs.